Lepidopteran fauna of Mandaitivu Mangrove Ecosystem, Jaffna, Sri Lanka - G. W. A. L. K., Wijewantha; Gnaneswaran, R. (University of Jaffna, 2023)
The mangrove forests, which support the survival of both terrestrial and aquatic inhabitants, are considered some of the most productive ecosystems. Mangrove faunal diversity is well known for the vertebrates and invertebrates but is poorly known for insects. Mangroves and insects have strong relationships in which mangroves provide a suitable habitat for insect habitation. In contrast, the feeding activities of insects contribute to the litter detritus formation and sustainability of the mangrove ecosystem. They connect mangroves with adjoined terrestrial and marine ecosystems by their eco-services such as pollination, herbivory, predation, and being food for other predators. Lepidopterans, consisting of moths and butterflies, are the most widely recognized insects as indicators of the ecosystem's health and are considered in conservation strategies. As the information on the Lepidopteran fauna of mangrove has not been revealed in Sri Lanka, this study was performed to explore the diversity of butterflies and moths in the Mandaitivu mangrove ecosystem from August 2019 to March 2020 located in the Northern Province of Sri Lanka. True mangrove species such as Avicennia marina, Rhizophora mucronata, Ceriops tagal and Pemphis acidula are distributed as patches around this island. Adult as well as larval stages of butterflies and moths were collected from two different locations based on the abundance of the mangrove vegetation at the west and south border of the Mandaitivu Island through sweep netting and handpicking methods. They were then identified based on their morphological characteristics. A total of 13 butterfly species, belonging to four families, and 6 moth species, belonging to three families were recorded. The highest species composition was recorded from Avicennia marina than Rhizophora mucronata which has fewer insects probably due to the thickness of their leaves. The plain tiger (Danaus chrysippus) was the most common and abundant butterfly followed by Mottled Emigrant (Catopsilia pyranthe) and the Small Salmon Arab (Colotis amata). The Yellow Pansy (Junonia hierta), the critically endangered (CR) species was also found. The other twelve species are listed as least concerned (LC) nationally. All the moth species recorded are listed as not assessed as per the IUCN red list. These results confirm that further extensive surveys in the Mandaitivu mangrove ecosystem will expose more diverse assemblages of lepidopterans that can be utilized in threat assessment and conservation strategy planning.
Keywords: Butterfly; Moth; Mangrove ecosystem